Measurement of Blood Pressure as Cardiovascular Risk in Stable COPD Patients (Medicine Today, 2017)
COPD is one of the major cause of chronic morbidity and mortality throughout the world. Among the extra pulmonary effects of COPD cardiovascular disorders are significant. Although its silent involvement is known, but little attention paid to this major comorbidity while treating these group of patients. To assess the cardiovascular risk even in stable COPD patients their systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), mean arterial pressure (MAP) were observed and correlated these with the severity of airflow limitation (FEV1). This crosssectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January to December, 2010. For this purpose 60 (sixty) male, smoker (5-10 pack year) patients of stable COPD (FEV1/FVC%